A Study on the effect of Kenya's land policies on the land rights of Kenyan women - Mutida, Adelide Kamanthe (KDI School, 2011)
Historically, women in Kenya have been denied their land rights through discriminative land policies and laws which as a result have made them worse off and structurally dependent upon Kenyan men. The need to address this gender disparity in land ownership grows from the recognition that past land policies have systemically marginalized women from access to and control over land. This denial of equal property rights has put Kenyan women at a greater vulnerability to poverty, disease, violence, and homelessness compared to Kenyan men. This research paper argues that this situation is a direct consequence of discriminatory laws and practices. In 2010, Kenyans adopted a new constitution which is laudable in its efforts to address most, if not all, of the issues that have perturbed Kenyan women over the years. The new laws have instilled faith in the forlorn process of political, social and economic change in Kenya. Nonetheless making laws and implementing laws are entirely different processes and the real test lies with the latter. Based on findings and analysis, this research paper identifies those challenges and hurdles that stand in the way of true change in terms of implementation and provides policy recommendations on how to combat those challenges.
Thesis(Master) --KDI School:Master of Public Policy,2011